49.3k views
3 votes
Acos²theta + Bsin²theta = C
Show that
tan²theta =C- A/B-C​

User Lalle
by
6.0k points

1 Answer

4 votes


Tan^2x= (C -A)/((B-C))

Explanation:

Here we have , Acos²theta + Bsin²theta = C or ,
Acos^2theta + Bsin^2theta = C

Let theta = x , So
Acos^2x + Bsin^2x = C . Let's solve it further


Acos^2x + Bsin^2x = C


(Acos^2x)/(cos^2x) + (Bsin^2x)/(cos^2x) = (C)/(cos^2x)


A + B((sin^2x)/(cos^2x)) = C(1)/(cos^2x) {
(sin^2x)/(cos^2x) = Tan^2x , (1)/(cos^2x) = sec^2x }


A + B(Tan^2x) = C(sec^2x) {
sec^2x=1+Tan^2x }


A + B(Tan^2x) = C( 1+Tan^2x )


A + B(Tan^2x) = C+C(Tan^2x )


B(Tan^2x)-C(Tan^2x ) = C -A


(B-C)(Tan^2x)= C -A


Tan^2x= (C -A)/((B-C))

Therefore ,
Tan^2x= (C -A)/((B-C)) .

User Meefte
by
6.1k points